KIF15 Promotes Progression of Castration Resistant Prostate Cancer by Activating EGFR Signaling Pathway - Gao, Lin; Zhao, Ru; Liu, Junmei; Zhang, Wenbo; Sun, Feifei; Yin, Qianshuo; Wang, Xin; Wang, Meng; Feng, Tingting; Qin, Yiming; Cai, Wenjie; Li, Qianni; et al. (Frontiers in Oncology, 2021)
Castration-resistant prostate cancer (CRPC) continues to be a major clinical problem and its underlying mechanisms are still not fully understood. The epidermal growth factor receptor (EGFR) activation is an important event that regulates mitogenic signaling. EGFR signaling plays an important role in the transition from androgen dependence to castration-resistant state in prostate cancer (PCa). Kinesin family member 15 (KIF15) has been suggested to be overexpressed in multiple malignancies. Here, we demonstrate that KIF15 expression is elevated in CRPC. We show that KIF15 contributes to CRPC progression by enhancing the EGFR signaling pathway, which includes complex network intermediates such as mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K)/AKT pathways. In CRPC tumors, increased expression of KIF15 is positively correlated with EGFR protein level. KIF15 binds to EGFR, and prevents EGFR proteins from degradation in a Cdc42-dependent manner. These findings highlight the key role of KIF15 in the development of CRPC and rationalize KIF15 as a potential therapeutic target.